PHONETIC STYLISTIC DEVICES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Phonetic stylistic devices - powerful tool for writers to create specific sound or rhythm in writing Manipulate sounds of language (vowels, consonants) to evoke emotions, create atmosphere.Add depth, complexity, engage reader on sensory level. From alliteration, assonance to onomatopoeia, rhythm - crucial in shaping overall tone, impact of writing.Guide explores various phonetic stylistic devices, how they enhance writing quality